Amyotrophic lateral sclerosis in Africa: a multi-center cohort study, ALS and related syndromes under the tropics (TROPALS) collaboration - (:unkn) unknown (My University, 2017)
Background:The literature on amyotrophic lateral sclerosis (ALS) in Africa is limited. A few studies have been performed, mostly case series with variable methodology, sample sizes and data collection (1). In recent years, there has been increased interest in the epidemiologic and phenotypic variability of ALS among different populations (23).Objective:We aimed to describe and compare demographics, clinical features, management and survival of ALS in Africa.Methods:A hospital-based multi-centre cohort study was undertaken in African countries. ALS patients diagnosed from 2005 to 2017 in the participant centres were included. An ALS expert neurologist confirmed the diagnosis through medical records. Patients were categorized at diagnosis according to El Escorial revised criteria and follow-up assessments were performed. Descriptiveand analytical statistics were conducted. Subgroup analyses were performed according to subcontinent, based on the United Nations Statistics Division. Survival analyses were carried out with the Kaplan-Meier method.Results:10 centres from 89 African countries participated. An overall 185 patients were included: 114 in Northern Africa, 30 in Southern Africa and 41 in Western Africa. A male predominance was found with a sex ratio (male/female) of 2.9 overall. Median age at onset was 54 years (interquartile range (IQR) 4 64). Western African patients had younger age at onset (47 years) compared with Northern and Southern Africa, p¼ 0.0001. Themedian diagnostic delay was 12 months. Onset was bulbar in 22.7% of cases. Median ALS Functional Rating Scale Revised (ALSFRS-R) was 38 at diagnosis. 59 cases presented with atypical signs (32%), of which nearly 40% had cognitive impairment. Concerning the management, 80% had a medical or traditional treatment. However, only 47 cases had access to riluzole, mostly in Northern Africa. Overall, the median survival sincediagnosis was 14 months. Longer survival was observed in Northern Afr
Keywords: African Research